Atrial fibrillation and cancer; understanding the mysterious relationship through a systematic review - Noman Lateef; Vikas Kapoor; Muhammad Junaid Ahsan; Azka Latif; Umair Ahmed; Mohsin Mirza; Faiz Anwar; Mark Holmberg (Greater Baltimore Medical Center, 2020)
Background Atrial Fibrillation (AFib) is the most common cardiac arrhythmia, occurring in ≈1% of the general population. An increased risk of malignancy among patients with AFib would be of substantial public health importance, given the high prevalence and associated economic burden of both disorders. Objectives To evaluate the relationship between atrial fibrillation (AFib) and cancer. Methods We conducted an extensive database search on PubMed, Google Scholar, ScienceDirect, and SEER Database from their inception to September 2019 for any study that evaluated the association between AFib and cancer. Results In the first 3 months of AFib diagnosis, Ostenfeld et al. reported an absolute cancer risk of 2.5% with a standardized incidence ratio of 7.02 and 3.53 for metastatic and localized cancer, respectively. Likewise, Saliba et al. detected an increase in the odds of cancer diagnosis in first 90 days after AF diagnosis with OR of 1.85. Moreover, in another study new-onset breast and colorectal cancer was especially associated with AF in the first 90 days after diagnosis with HR of 3.4 but not thereafter (HR 1.0). Similarly, Conen et al. reported high relative risk of cancer with HR of 3.54 in the first 3 months after new-onset AFib. However, beyond the initial 90 day period, the risk of cancer in AFib is only slightly increased. Conclusion Based on our review, there appears to be an increase in risk of subsequent diagnosis of cancer in patients with AF, likely owing to the shared risk factors between the two conditions. While the results of this study raise interesting questions for future search, they are not currently strong enough to justify initiating cancer screening for an occult cancer in a patient with AF. Regardless, measures to target modification of these shared risk factors remains an important consideration.